ORGAN DONATION AND TRANSPLANTATION IN RUSSIAN FEDERATION IN 2015. 8th report of National Register - S. V. Gautier (Vestnik Transplantologii i Iskusstvennyh Organov, 2016)
Aim. To carry out monitoring of the organization and development of the organ donation and transplantation in theRussian Federationaccording to 2015.Materials and methods. Questioning of heads of all the centers of transplantation is carried out. The comparative analysis of the obtained data in dynamics by years, between certain regions of theRussian Federation, the transplantation centers is done.Results. According to the register in2015 inthe Russian Federation 36 centers of renal transplantation, 17 centers of liver transplantation and 10 centers of heart transplantation were functioning. The waiting list of kidney transplantation in 2015 included 4167 potential recipients that make 13% of the total number of the patients (31 500) receiving a dialysis. The rate of donor activity in 2015 made 3.0 pmp. Efficiency of donor programs in 2015 continues to increase: the share of multiorgan retrievals made 57.8%, average number of organs, received from one effective donor, made 2.7. In 2015 the rate of kidney transplantation made 6.5 pmp; the rate of liver transplantation made 2.2 pmp; the rate of heart transplantation made 1.2 pmp. The number of transplantations of liver and heart in theRussian Federationcontinues to increase. The number of transplantations of kidney remains approximately at one level in the range of 950–1050.Moscowcapital region continues to be the center of stability and development of the organ donation and transplantation in the country, in which 10 centers of transplantation are functioning and nearly a half from all kidney transplantations and more than 65% of all liver and heart transplantations are carried out.Conclusion. The potential for further development of the transplantation care in theRussian Federationcontinues to persist. In particular, at the expense of increasing efficiency of regional donation programs, expanding practices of multiorgan recuperation and transplantations of extrarenal organs, through interregional transplant coordination. It is critical to keep the volumes of the state order to deliver transplantological medical care to the population and to implement federal funding to conduct donation programs.